2010
DOI: 10.1007/s10532-010-9418-0
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic analysis of three modified novel nitroreductases

Abstract: A kinetic comparison between three nitroreductase enzymes isolated from the genome of Bacillus licheniformis ATCC 14580 for prospective use as immobilised enzymes for explosives detection has been conducted. The genes encoding the three enzymes (yfkO [BLNfnB] encoding an NfsB-like enzyme; nfrA [BLNfrA1] and ycnD [BLNfrA2] encoding PnrA-like enzymes) have been PCR amplified from the native genome and cloned into pET-28a(+) and a modified cysteine((6))-tagged pET-28a(+) and subsequently over-expressed, purified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…However, in contrast to the results obtained by Gwenin et al, no enzymatic activity was detected toward non-aromatic compounds such as HMX, RDX, and nitroglycerine. However, three enzymes belonging to the NTR family, cloned from Bacillus licheniformis, are not active against non-aromatic nitro compounds [23]. The substrate specificity profiles for different enzymes from different sources indicated that NTRs could be used for the detection of not only TNT and tetryl, but also other explosive materials.…”
Section: Substrate Specificity Profile Of E Coli Ntrmentioning
confidence: 99%
“…However, in contrast to the results obtained by Gwenin et al, no enzymatic activity was detected toward non-aromatic compounds such as HMX, RDX, and nitroglycerine. However, three enzymes belonging to the NTR family, cloned from Bacillus licheniformis, are not active against non-aromatic nitro compounds [23]. The substrate specificity profiles for different enzymes from different sources indicated that NTRs could be used for the detection of not only TNT and tetryl, but also other explosive materials.…”
Section: Substrate Specificity Profile Of E Coli Ntrmentioning
confidence: 99%
“…Type II enzymes catalyse single-electron transfer to produce a nitro anion radical, which can reduce nitro group to a nitroso group. Under aerobic conditions, however, the nitro anion radical reacts with oxygen and produces superoxide anion in a futile cycle 20 .…”
Section: Nitroreductasesmentioning
confidence: 99%
“…Nitroreductases (NTR) are a family of proteins involved in the reduction of nitro-containing compounds [ 1 ]. The flexibility of these enzymes comprises their usefulness in a variety of biological and medical applications.…”
Section: Introductionmentioning
confidence: 99%